Importance of Follow-Up Cerebrospinal Fluid Analysis in Cryptococcal Meningoencephalitis. (13th October 2014) - Skripuletz, Thomas; Schwenkenbecher, Philipp; Pars, Kaweh; Stoll, Matthias; Conzen, Josef; Bolat, Seza; Pul, Refik; Vonberg, Ralf-Peter; Sedlacek, Ludwig; Wurster, Ulrich; Stangel, Martin; Trebst, Corinna
Abstract : Cryptococcal meningoencephalitis represents a serious infection of the central nervous system, where reliable prognostic factors during the disease course are needed. Twenty-one patients diagnosed with cryptococcal meningoencephalitis in a German university hospital from 1999 to 2013 were analysed retrospectively. CSF parameters were analysed prior to therapy and during antifungal treatment and were compared between patients who survived or deceased. Fifteen patients clinically improved after antifungal therapy, while six patients died. No differences were observed between the outcome groups for the CSF parameters cell count, lactate, total protein, and CSF-serum albumin quotients (QAlb). Follow-up examinations of serum cryptococcal antigen titer and CSF cell count have shown that these parameters cannot be used to monitor the efficacy of antifungal therapy as well. In contrast, the course of QAlb during therapy was indicative for the outcome as a possible prognostic marker. In patients with clinical improvement QAlb values were falling under therapy, while rising QAlb values were found in patients with fatal outcome indicating a continuing dysfunction of the blood-CSF barrier. In conclusion, our results indicate that, among the various CSF parameters, the course of QAlb presents a promising marker that might be used to monitor the efficacy of antifungal therapy.